IDENTIFIKASI MISKONSEPSI MATERI IKATAN KIMIA MENGGUNAKAN TES DIAGNOSTIK PILIHAN GANDA TIGA TINGKAT (THREE TIER) PADA PESERTA DIDIK KELAS X MIA SMA NEGERI 8 PEKANBARU - Siti Azura; Jimmi Copriady; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aims of this research was to determine and amount of the misconception rate in X MIA class of Senior High School Negeri 8 Pekanbaru on chemical bonding. The research has been done in January-May 2017 by using descriptive method with simple random sampling to determined by Krejcie and Morgan formulas, the total of samples are 136 students. The instrument is a Three-Tier Diagnostic Test. Validating of instrument through content validity by material expert, construct validity using product moment correlation,and reliability using split half. Research result shown that the instrument was good and valid with instrument reliability value was 0,623, the percentage of students who had misconceptions 39,90% and including misconceptions medium category. Students, misconception that: (1) stability elements and octet rules misconceptions low category, (2 )drawing of Lewis symbol and structures misconceptions medium category, (3) ionic bonding and covalent bonding misconceptions medium category, (4) physical properties of ionic and covalent compounds misconceptions medium category,(5) metalic bonding misconceptions medium category, (6) polar and nonpolar covalent misconceptions medium category, (7) exclusion and failure octet rule misconceptions low category.Key Words : Misconception, Three tier diagnostic test, Chemical bonding